Packaging material, packaging bag, and manufacturing method of packaging material
The packaging material, with its specific layer configuration of ethylene vinyl acetate copolymer resin in the heat seal layer and cellulose and urethane resins in the surface and printing layers, addresses the limitations of existing packaging materials by enhancing piercing, blocking, heat, and water friction resistance while maintaining heat sealing and water vapor barrier properties.
Patent Information
- Application Number
- JP2023164660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing packaging materials using paper base materials lack excellent piercing resistance, blocking resistance, heat resistance, and water friction resistance while maintaining heat sealing properties and water vapor barrier properties.
A packaging material configuration comprising a heat seal layer, a paper base material, a printing layer, and a surface protective layer, where the heat seal layer includes ethylene vinyl acetate copolymer resin, the surface protective layer contains a cellulose resin and a plasticizer, and the printing layer includes a cellulose resin and a urethane resin.
The packaging material achieves excellent piercing resistance, blocking resistance, heat resistance, and water friction resistance while maintaining heat sealing properties and water vapor barrier properties.
Smart Images

Figure 2025055368000001 
Figure 2025055368000002 
Figure 2025055368000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a packaging material and a packaging bag that are excellent in puncture resistance, blocking resistance, heat resistance, and water friction resistance while maintaining heat sealability and water vapor barrier properties, and a manufacturing method that can provide the packaging material. [Background technology]
[0002] In recent years, it has become common for product packages and other wrapping materials to be printed for decoration and surface protection. Furthermore, the quality of printing, such as the design, beauty, and luxury of the printed matter, can stimulate consumer purchasing motivation and is of great industrial value.
[0003] Conventionally, laminate packaging materials using plastic films have been mainly used to construct packages. For example, Patent Document 1 describes an invention related to a laminate packaging material consisting of a base material, a print layer, an adhesive layer, and a sealant layer, in which biomass resin is used in the print layer and the adhesive layer. However, laminate packaging materials use a large amount of plastic film made of petroleum-derived materials, and from the viewpoints of reducing plastic, being environmentally friendly, and being carbon neutral, there is a demand for a change to paper (paper-based packaging materials), and technological developments are being made.
[0004] For example, Patent Document 2 describes an invention relating to a paper laminate having a resin layer, a printed layer, a paper substrate layer, a metal deposition film layer, a gas barrier coating layer, and a heat-sealable resin layer in that order, as an example of using a paper substrate as part of a packaging material. However, the resin layer formed on the printed layer is formed of low-density polyethylene or the like to impart heat sealability. Therefore, the hardness, toughness, and surface smoothness of the coating film are insufficient, and there are problems with puncture resistance, blocking resistance, and heat resistance. In addition to the above problems, paper packaging materials are required to have water vapor barrier properties.
[0005] For example, Patent Document 3 describes an invention relating to a packaging material having a surface protective layer, a printing layer, a paper base layer, and a resin layer in that order, the surface protective layer containing nitrocellulose. However, since the surface protective layer is formed only from nitrocellulose, the surface protective layer is insufficient in terms of smoothness, tack loss, and toughness, and has problems with water friction resistance, blocking resistance, and heat resistance.
[0006] That is, no packaging material using a paper base material has yet been found that has excellent puncture resistance, blocking resistance, heat resistance, and water-friction resistance while maintaining heat sealability and water vapor barrier properties. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-051796 A [Patent Document 2] JP 2006-256198 A [Patent Document 3] JP 2020-55171 A Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a packaging material and a packaging bag that are excellent in puncture resistance, blocking resistance, heat resistance, and water-friction resistance while maintaining heat sealability and water vapor barrier properties. [Means for solving the problem]
[0009] As a result of extensive research into the above problems, the present inventors have found that the above problems can be solved by using the packaging material described below, and have thus completed the present invention.
[0010] That is, the present invention provides a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, the heat seal layer comprises at least one selected from the group consisting of ethylene-vinyl acetate copolymer resins, acrylic resins, and ethylene-based ionomers, The present invention relates to a packaging material, wherein the surface protective layer comprises a cellulose-based resin (A) and a plasticizer.
[0011] The present invention also relates to the packaging material, wherein the surface protective layer has a gloss value of 15 or more as measured in accordance with JIS Z 8741.
[0012] The present invention also relates to the packaging material, wherein the content of the plasticizer in the surface protective layer is 0.1 to 20% by mass.
[0013] The present invention also relates to the packaging material, wherein the plasticizer comprises at least one plasticizer selected from the group consisting of citric acid esters, phthalic acid esters, phosphate esters, trimellitic acid esters, aliphatic dibasic acid esters, glycol ethers, sulfonic acid amides, and castor oil.
[0014] The present invention also relates to the packaging material, wherein the heat seal layer contains an ethylene-vinyl acetate copolymer resin and / or an ethylene-based ionomer.
[0015] The present invention also relates to the packaging material, wherein the viscosity of the cellulose-based resin (A) measured in accordance with JIS K 6703 satisfies any one of the following (1) to (3): (1) The viscosity at a solution concentration of 12.2% by mass is 1.5 to 16 seconds. (2) The viscosity at a solution concentration of 20.0% by mass is 3.0 to 40 seconds. (3) The viscosity at a solution concentration of 25.0% by mass is 0.1 to 22 seconds.
[0016] The present invention also relates to the packaging material described above, further comprising a barrier layer.
[0017] The present invention also relates to the packaging material, wherein the cellulose-based resin (A) contains a nitrocellulose resin.
[0018] The present invention also relates to the packaging material, wherein the printed layer contains a cellulose-based resin (B).
[0019] The present invention also relates to the packaging material, wherein the printed layer further contains at least one resin (C) selected from the group consisting of polyamide resins, urethane resins, styrene-maleic acid copolymer resins, styrene-allyl alcohol copolymer resins, and acrylic resins.
[0020] The present invention also relates to the packaging material, wherein a mass ratio of the cellulose-based resin (B) to the resin (C) is from 99:1 to 30:70.
[0021] The present invention also relates to the packaging material, wherein the surface protective layer further contains a polyamide resin.
[0022] The present invention also relates to the packaging material, wherein a mass ratio of the cellulose-based resin (A) to the polyamide resin is from 99:1 to 15:85.
[0023] The present invention also relates to the packaging material, wherein the surface protective layer further contains amide wax.
[0024] The present invention also relates to a packaging bag formed from the packaging material.
[0025] The present invention also provides a method for producing a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, comprising the steps of: A step of gravure printing a printing ink onto one side of a paper substrate to form a printing layer; A step of forming a surface protective layer by gravure printing an overcoat agent containing a cellulose-based resin (A) and a plasticizer on the printing layer; and The present invention relates to a method for producing a packaging material, which includes a step of coating the other side of a paper substrate with a heat-sealing agent containing at least one member selected from the group consisting of ethylene-vinyl acetate copolymer resin, acrylic resin, and ethylene-based ionomer to form a heat-sealing layer. Effect of the Invention
[0026] According to the present invention, it is possible to provide a packaging material and a packaging bag that are excellent in puncture resistance, blocking resistance, heat resistance, and water-friction resistance while maintaining heat sealability and water vapor barrier properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] <Packaging material> The packaging material of the present invention has a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, and is characterized in that the heat seal layer contains at least one selected from the group consisting of ethylene-vinyl acetate copolymer resin, acrylic resin, and ethylene-based ionomer, and the surface protective layer contains a cellulose-based resin (A) and a plasticizer. By adopting the above-mentioned configuration, the packaging material has good hardness, flexibility, toughness, and surface smoothness, and can exhibit excellent puncture resistance, blocking resistance, heat resistance, and water friction resistance. The following describes in detail an embodiment of the present invention. However, the description of the components described below is an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention. In this specification, "parts" and "%" refer to "parts by mass" and "% by mass" unless otherwise specified. In addition, the packaging material may be abbreviated simply as "laminate", but this has the same meaning. In addition, "solid content" refers to the total mass of non-volatile components. In this specification, the term "printing ink" refers to a material containing a colorant such as a pigment, whereas the term "overcoat agent" refers to a material not containing a colorant such as a pigment, but does not exclude a material containing a small amount of colorant unintentionally mixed therein.
[0028] <Surface protective layer> The surface protective layer in the present invention contains a cellulose-based resin (A) and a plasticizer. The surface protective layer can be formed by an overcoat agent containing a cellulose-based resin (A) and a plasticizer. The method for forming the surface protective layer can be appropriately selected from known printing methods such as gravure printing and flexographic printing, and is preferably gravure printing. From the viewpoint of printability, the viscosity of the overcoat agent is preferably 20 to 200 mPa·s. The thickness of the surface protective layer is preferably from 0.3 to 10 μm, and more preferably from 1 to 7 μm.
[0029] [Overcoat agent] The overcoat agent contains a cellulose-based resin (A) and a plasticizer, and may further contain an organic solvent.
[0030] (Cellulosic resin (A)) As the cellulose-based resin (A), cellulose ester resin is suitable. The cellulose ester resin is a resin obtained by esterification of cellulose derived from non-edible plants such as wood fiber and cotton, and examples thereof include cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, and nitrocellulose. As the cellulose ester resin, nitrocellulose is preferred from the viewpoint of heat resistance.
[0031] The content of the cellulose-based resin (A) in the surface protective layer is preferably 5 to 85% by mass, more preferably 10 to 60% by mass, and particularly preferably 10 to 40% by mass. The content of the cellulose-based resin (A) in the resin contained in the surface protective layer is preferably 15 to 99% by mass, more preferably 15 to 50% by mass, and particularly preferably 15 to 30% by mass. When it is in the above range, it is possible to achieve both hardness and toughness of the surface protective layer, and blocking resistance and heat resistance are improved.
[0032] The cellulose-based resin (A) preferably has a viscosity measured in accordance with JIS K 6703-1995 that satisfies any one of the following (1) to (3). The viscosity is the time it takes for a steel ball to fall into an isopropanol solution of the cellulose-based resin (A) (steel ball falling time (seconds)). (1) The viscosity at a solution concentration of 12.2% is 1.5 to 16 seconds. (2) The viscosity at a solution concentration of 20.0% is 3.0 to 40 seconds. (3) The viscosity at a solution concentration of 25.0% is 0.1 to 22 seconds. In particular, the viscosity of the cellulose-based resin (A) preferably satisfies the above (3). In the above (3), the viscosity at a solution concentration of 25.0% is preferably 0.5 to 15 seconds, more preferably 0.5 to 9 seconds. When the viscosity is in the above range, the surface protection layer is provided with surface smoothness and toughness, and the water friction resistance and heat resistance are improved.
[0033] The weight average molecular weight (Mw) of the cellulose-based resin (A) is preferably 5,000 to 200,000, more preferably 10,000 to 100,000, and even more preferably 10,000 to 80,000. When it is within the above range, the coating film can have both hardness and flexibility, and the puncture resistance, blocking resistance, and adhesion between the surface protective layer and the printing layer are improved. The glass transition temperature of the cellulose-based resin (A) is preferably 80° C. to 160° C. When it is within the above range, the surface protective layer can have both hardness and flexibility, and the puncture resistance, blocking resistance, and adhesion between the surface protective layer and the printing layer are improved.
[0034] The weight average molecular weight can be measured, for example, by GPC (gel permeation chromatography), and can be calculated as a molecular weight converted using polyethylene glycol as a standard substance. The measuring device can be a GPC device such as Shodex GPC-104 manufactured by Showa Denko K.K., and the column can be a Shodex LF-404 manufactured by Showa Denko K.K., and the detector can be an RI (differential refractometer), and the measurement temperature is preferably a column temperature of 20 to 50°C. The eluent can be tetrahydrofuran, and the flow rate is generally in the range of 0.2 to 5.0 mL / min.
[0035] The glass transition temperature can be measured, for example, using a differential scanning calorimeter (DSC measuring device, Shimadzu Corporation's "DSC-60A"), and the temperature of the inflection point in the baseline shift can be used as the glass transition temperature. The measurement is preferably performed in a nitrogen atmosphere, with the measurement temperature range being -100 to 200°C and the heating rate being 1 to 5°C / min.
[0036] When the cellulose-based resin (A) is nitrocellulose, the nitrogen content of the nitrocellulose is preferably 10 to 13 mass% of the total solid content of the nitrocellulose, and more preferably 10.7 to 12.2 mass%. When it is in the above range, the hardness and flexibility of the surface protective layer can be compatible, and the puncture resistance, blocking resistance, and adhesion between the surface protective layer and the printing layer are improved.
[0037] The weight average molecular weight of the nitrocellulose is preferably 3,000 to 40,000, more preferably 3,000 to 25,000, and even more preferably 5,000 to 15,000. When it is within the above range, the surface protective layer can have both hardness and flexibility, and the puncture resistance, blocking resistance, and adhesion between the surface protective layer and the printing layer are improved. Commercially available nitrocellulose products include, for example, those manufactured by NOBEL (DHX3-5, DHX5-10, DHX8-13).
[0038] (Plasticizer) The plasticizer, even in small amounts, promotes the volatility of the organic solvent, imparts flexibility to the surface protective layer, and enhances adhesion to the printed layer. The inclusion of the cellulose-based resin (A) and the plasticizer improves blocking resistance, contributing to solving the problem. As the plasticizer, in addition to the cellulose resin (A), one that has excellent compatibility with other resin components contained in the surface protective layer and has low volatility is preferably used, and for example, it is preferable to include at least one selected from citrate esters, phthalate esters, phosphate esters, trimellitic acid esters, aliphatic dibasic acid esters, glycol ethers, sulfonamides, and castor oil, and glycol ethers are more preferable. Note that the plasticizer refers to one that remains in the surface protective layer and exerts the above-mentioned effect. For example, even if an organic solvent has a similar chemical structure to the above-mentioned plasticizer, it is difficult to exert the effect if it is almost completely volatilized from the surface protective layer, and such an organic solvent cannot be called a plasticizer.
[0039] As the citrate ester, acetyl trialkyl citrate such as triethyl citrate, acetyl triethyl citrate, tri n-butyl citrate, acetyl tri n-butyl citrate, and acetyl citrate-2-ethylhexyl is preferred. The alkyl group preferably has a carbon number of 2 to 12. Among them, acetyl tri n-butyl citrate, acetyl triethyl citrate, and the like are preferably used. Examples of phthalate esters include dialkyl phthalates such as bis(2-ethylhexyl) phthalate, diisononyl phthalate, diisodecyl phthalate, and diundecyl phthalate, and the alkyl group preferably has a carbon number of 2 to 12. Among these, diisononyl phthalate, diisodecyl phthalate, and the like are preferably used. Suitable examples of the phosphate ester include tricresyl phosphate, triphenyl phosphate, tributyl phosphate, and the like, and more preferably tributyl phosphate. As the trimellitic acid ester, trialkyl trimellitates such as tri-2-ethylhexyl trimellitate, trioctyl trimellitate, and triisononyl trimellitate are preferred. The alkyl group preferably has a carbon number of 2 to 12. Among them, tri-2-ethylhexyl trimellitate and the like are preferably used. The aliphatic dibasic acid ester is preferably a fatty acid dialkyl ester, and the alkyl group preferably has a carbon number of 2 to 12. Examples of the fatty acid dialkyl ester include an adipate ester and a sebacate ester, and among these, bis(2-ethylhexyl) adipate, diisononyl adipate, diisodecyl adipate, bis(2-ethylhexyl) sebacate, diisononyl sebacate, and diisodecyl sebacate are preferably used. Preferred examples of the sulfonic acid amide include N-butylbenzenesulfonic acid amide and N-ethyltoluenesulfonic acid amide. Examples of the glycol ether include diethylene glycol monobutyl ether and diethylene glycol monoethyl ether.
[0040] The content of the plasticizer in the surface protective layer is preferably 0.1 to 20% by mass, more preferably 3 to 15% by mass, and particularly preferably 5 to 12% by mass. When the content is within the above range, the surface protective layer can have both hardness and toughness, and has improved blocking resistance, puncture resistance, and heat resistance.
[0041] The surface protective layer of the packaging material of the present invention preferably has a gloss value of at least 15. More preferably, it is from 20 to 60, and even more preferably, it is from 35 to 50. The gloss value is a 60 degree gloss value (Gs(60)) measured in accordance with JIS Z 8741:1997. The gloss value mentioned above does not refer to the glossiness (mirror reflection) of a metal layer such as an aluminum vapor deposition layer on the inside of the packaging material, but refers to the glossiness of the outermost surface protective layer. From the viewpoint of setting the gloss value of the surface protective layer within the above range, the surface protective layer preferably further contains a polyamide resin in addition to the cellulose-based resin (A) and the plasticizer. Also, from the viewpoint of blocking resistance and heat resistance, the surface protective layer preferably further contains an amide wax.
[0042] (Polyamide resin) As described above, from the viewpoint of achieving a gloss value of 15 or more, the surface protective layer of the present invention preferably further contains a polyamide resin in addition to the cellulose-based resin (A) and a plasticizer. The polyamide resin is not particularly limited, but is preferably a thermoplastic polyamide that is soluble in an organic solvent, and a polycondensation product of a polybasic acid and a polyamine is preferably used. Among them, polyamide resins containing a reaction product of an acid component containing polymerized fatty acid and / or dimer acid with an aliphatic and / or aromatic polyamine are preferred, and those containing a portion of primary and secondary monoamines are more preferred. Note that the polyamide resin referred to here is one having a weight average molecular weight of 1000 or more, and the amide wax is one having a weight average molecular weight of less than 1000.
[0043] Examples of polybasic acids used as raw materials for polyamide resins include adipic acid, sebacic acid, azelaic acid, phthalic anhydride, isophthalic acid, suberic acid, glutaric acid, fumaric acid, pimelic acid, oxalic acid, malonic acid, succinic acid, maleic acid, terephthalic acid, 1,4-cyclohexyldicarboxylic acid, trimellitic acid, dimer acid, hydrogenated dimer acid, and polymerized fatty acid. Among these, dimer acid and polymerized fatty acid are preferably used. The polyamide resin preferably has a structure derived from a polymerized fatty acid or a (hydrogenated) dimer acid, and preferably contains 50% by mass or more of structures derived from dimer acid and polymerized fatty acid in the polyamide resin. Here, the polymerized fatty acid is obtained by a cyclization reaction of an unsaturated fatty acid, and includes monobasic fatty acid, dimerized polymerized fatty acid (dimer acid), trimerized polymerized fatty acid, etc. When using a polymerized fatty acid, it is preferable to use a monobasic fatty acid including an unsaturated fatty acid or one obtained by ester polymerization thereof, and it is preferable to use one obtained by polymerization of an unsaturated fatty acid having 16 to 22 carbon atoms or an ester thereof. The polymerized fatty acid may be used alone or in combination of two or more kinds in any ratio. The fatty acids constituting the dimer acid or polymerized fatty acid are preferably those derived from natural oils such as soybean oil, palm oil, and rice bran oil, and more preferably those derived from oleic acid and linoleic acid. The polybasic acid may be used in combination with a monocarboxylic acid, such as acetic acid, propionic acid, lauric acid, palmitic acid, benzoic acid, or cyclohexane carboxylic acid.
[0044] The polyamines may include, for example, polyamines, primary or secondary monoamines. Examples of the polyamine include aliphatic diamines such as ethylenediamine, propylenediamine, hexamethylenediamine, and methylaminopropylamine; aliphatic polyamines such as diethylenetriamine and triethylenetetramine; alicyclic polyamines such as cyclohexylenediamine and isophoronediamine; aromatic aliphatic polyamines such as xylylenediamine; and aromatic polyamines such as phenylenediamine and diaminodiphenylmethane. Examples of primary and secondary monoamines include n-butylamine, octylamine, diethylamine, monoethanolamine, monopropanolamine, diethanolamine, and dipropanolamine. From the viewpoints of adhesiveness, blocking resistance, oil resistance, and heat resistance, it is preferable that the polyamide resin has a hydroxyl group in the molecule, and it is preferable to use an alkanolamine as the primary or secondary monoamine component.
[0045] As commercially available polyamide resins, for example, the Vegichem Green series (manufactured by Tsuno Food Industries Co., Ltd.) and the Newmide series (manufactured by Harima Chemicals Co., Ltd.) can be used.
[0046] The softening point of the polyamide resin is preferably 80 to 140° C., and more preferably 90 to 120° C. When the softening point is 80° C. or higher, the surface protective layer is easily detackified and blocking can be suppressed. When the softening point is 140° C. or lower, the surface protective layer becomes flexible and the adhesion between the surface protective layer and the printing layer is improved. From the viewpoint of the solubility of the polyamide resin, the weight average molecular weight of the polyamide resin is preferably in the range of 2,000 to 70,000, and more preferably 5,000 to 30,000. When the weight average molecular weight is 2,000 or more, the surface protective layer becomes strong and the heat resistance is improved. When the weight average molecular weight is 50,000 or less, the viscosity of the overcoat agent can be reduced, and the storage stability is improved. The softening point can be measured in accordance with JIS K 2207 (ring and ball method).
[0047] The mass ratio of the cellulose-based resin (A) to the polyamide resin in the surface protective layer is preferably 99:1 to 15:85, more preferably 50:50 to 15:85, and even more preferably 30:70 to 15:85. Within the above range, the surface protective layer has a good balance of hardness, toughness, and surface smoothness, and is excellent in blocking resistance and heat resistance.
[0048] (Other resins) The surface protective layer and the overcoat agent may contain other resins other than the cellulose resin (A) and the polyamide resin, so long as the effect of the present invention is not impaired. Examples of other resins include polylactic acid resin, urethane resin, vinyl chloride resin, vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-acrylic copolymer resin, rosin resin, vinyl acetate resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, acrylic resin, urethane-acrylic resin, styrene resin, styrene-acrylic acid resin, styrene-allyl alcohol resin, styrene-maleic acid resin, maleic anhydride resin, maleic acid resin, rosin-modified maleic acid resin, cycloolefin resin, dammar resin, polyester resin, alkyd resin, terpene resin, phenol-modified terpene resin, ketone resin, cyclized rubber, chlorinated rubber, butyral, polyacetal resin, silicone resin, and modified resins thereof.
[0049] (Organic solvent) The overcoat agent may contain an organic solvent. Examples of the organic solvent include hydrocarbons such as methylcyclohexane and ethylcyclohexane; ketones such as acetone, methyl ethyl ketone (MEK), and methyl isobutyl ketone; esters such as ethyl acetate, n-propyl acetate, and butyl acetate; and alcohols such as methanol, ethanol, propanol, isopropanol (IPA), and butanol. The organic solvent may be appropriately selected in consideration of reducing the amount of solvent remaining in the film after printing, and one type may be used alone, or two or more types may be mixed and used.
[0050] (Amide wax) As described above, from the viewpoint of blocking resistance and heat resistance, the overcoat agent and surface protective layer of the present invention preferably further contain an amide wax in addition to the cellulose-based resin (A) and the plasticizer. The amide wax has a weight-average molecular weight of less than 1000. The amide wax is a fatty acid amide, and preferably has a fatty acid residue and an amide group. It is believed that the fatty acid amide is oriented on the surface of the surface protective layer after printing, and exhibits slip properties to improve blocking resistance. Note that this explanation is based on technical considerations and does not limit the invention in any way.
[0051] Suitable examples of the fatty acid amide include monoamides, substituted amides, bisamides, methylol amides, and ester amides, and it is preferable that the fatty acid amide is at least one selected from the group consisting of monoamides, substituted amides, and bisamides.
[0052] The melting point of the fatty acid amide is preferably 50°C to 150°C. Examples of monoamides having a melting point of 50°C to 150°C include lauric acid amide (melting point 87°C), palmitic acid amide (melting point 100°C), stearic acid amide (melting point 101°C), behenic acid amide (melting point 110°C), hydroxystearic acid amide (melting point 107°C), oleic acid amide (melting point 75°C), and erucic acid amide (melting point 81°C). Examples of substituted amides having a melting point of 50°C to 150°C include N-oleyl palmitic acid amide (melting point 68°C), N-stearyl stearic acid amide (melting point 95°C), N-stearyl oleic acid amide (melting point 67°C), N-oleyl stearic acid amide (melting point 74°C), and N-stearyl erucic acid amide (melting point 69°C). Examples of bisamides having a melting point of 50°C to 150°C include methylene bisstearic acid amide (melting point 142°C), ethylene bisstearic acid amide (melting point 145°C), ethylene bishydroxystearic acid amide (melting point 145°C), ethylene bisbehenic acid amide (melting point 142°C), hexamethylene bisstearic acid amide (melting point 140°C), hexamethylene bisbehenic acid amide (melting point 142°C), hexamethylene hydroxystearic acid amide. amide (melting point 135°C), ethylene bis oleamide (melting point 119°C), ethylene bis erucamide (melting point 120°C), hexamethylene bis oleamide (melting point 110°C), N,N'-distearyl adipamide (melting point 141°C), N,N'-distearyl sebacamide (melting point 136°C), N,N'-dioleyl adipamide (melting point 118°C), and N,N'-dioleyl sebacamide (melting point 113°C). An example of the methylol amide having a melting point of 50° C. to 150° C. is methylol stearic acid amide (melting point: 110° C.). An example of an ester amide having a melting point of 50° C. to 150° C. is stearamide ethyl stearate (melting point: 82° C.). Among them, in order to maintain the laminate strength, those having a molecular weight of 200 to 800 are preferred, and those having a molecular weight of 250 to 700 are even more preferred.
[0053] The fatty acid constituting the fatty acid amide is preferably a saturated fatty acid having 12 to 22 carbon atoms and / or an unsaturated fatty acid having 16 to 25 carbon atoms, more preferably a saturated fatty acid having 16 to 18 carbon atoms and / or an unsaturated fatty acid having 18 to 22 carbon atoms. Particularly preferred saturated fatty acids are lauric acid, palmitic acid, stearic acid, behenic acid, and hydroxystearic acid, and particularly preferred unsaturated fatty acids are oleic acid and erucic acid. Among these, fatty acid amides consisting of at least one fatty acid selected from the group consisting of palmitic acid, stearic acid, behenic acid, hydroxystearic acid, oleic acid, and erucic acid are preferred, palmitic acid amide, erucic acid amide, and ethylene bis oleic acid amide are more preferred, and ethylene bis oleic acid amide is particularly preferred.
[0054] The content of the amide wax in the surface protective layer is preferably 0.1 to 22.5% by mass, more preferably 0.1 to 15% by mass, and even more preferably 0.1 to 7.5% by mass. When it is within the above range, it is possible to achieve both tack loss and toughness of the surface protective layer, and blocking resistance and heat resistance are improved.
[0055] (Additives) The surface protective layer may contain optional components such as additives within the range not impairing the effects of the present invention.
[0056] <Hydrocarbon wax particles> The overcoat agent and the surface protective layer preferably contain hydrocarbon wax particles, which improves the abrasion resistance of the surface protective layer. The hydrocarbon wax particles are preferably hydrocarbon-based wax particles having a hardness (penetration) of 0.5 to 12. Examples of the hydrocarbon wax particles include polyethylene wax, Fischer-Tropsch wax, paraffin wax, microstearate wax, and polypropylene wax. Among them, the hydrocarbon wax containing polyethylene wax is preferable. In the overcoat agent, the average particle size of the hydrocarbon wax particles is preferably 0.3 to 10 μm, more preferably 0.8 to 7 μm, and the content of the hydrocarbon wax particles in the surface protective layer is preferably 0.1 to 10 mass %, more preferably 0.5 to 7 mass %.
[0057] Chelating crosslinking agent The overcoat agent and the surface protective layer preferably contain a chelating crosslinking agent. Examples of the chelating crosslinking agent include titanium chelate and zirconium chelate. Examples of the titanium chelate include titanium alkoxides such as tetraisopropyl titanate, tetranormalbutyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, tetramethyl titanate, and tetrastearyl titanate, triethanolamine titanate, titanium acetylacetate, titanium tetraacetylacetonate, tetraisopropoxytitanium, titanium ethylacetoacetate, titanium lactate, octylene glycol titanate, n-butyl phosphate titanium, and propanedioxtitanium bis(ethyl acetylacetate). Examples of the zirconium chelate include zirconium propionate and zirconium acetylacetate. Among them, a chelating crosslinking agent that does not generate acetylacetone after the crosslinking reaction is preferable from the viewpoint of the environment.
[0058] The content of the chelating crosslinking agent in the surface protective layer is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass. When the content is 0.1% by mass or more, the heat resistance, oil resistance, and PVC blocking resistance are improved, and when the content is 5.0% by mass or less, the storage stability of the overcoat agent is excellent. By using these chelating crosslinking agents, the effect of improving the abrasion resistance of the formed coating is achieved.
[0059] <Print layer> The printing layer in the present invention is a layer containing a pigment and a binder resin, and is disposed on the surface of the paper substrate opposite to the surface having the heat seal layer. The printing layer is formed using a printing ink, and the printing method can be appropriately selected from known printing methods such as gravure printing and flexographic printing, and is preferably gravure printing. The thickness of the printing layer is preferably 0.1 to 10 μm, more preferably 0.3 to 6 μm, and particularly preferably 0.5 to 3 μm. In this specification, the term "printed layer" includes not only a single printed layer but also a layer in which multiple printed layers are laminated, and printed layers of different hues can be combined in any desired manner.
[0060] [Printing ink] The printing ink contains a pigment and a binder resin, and may further contain an organic solvent and any additives. From the viewpoints of pigment dispersibility and workability, the printing ink preferably has a viscosity at 25°C of 50 to 1,000 mPa·s.
[0061] (Pigments) Examples of pigments include organic pigments, inorganic pigments, and extender pigments. Organic pigments Examples of organic pigments include organic compounds and organic metal complexes, such as soluble azos, insoluble azos, azos, phthalocyanines, halogenated phthalocyanines, anthraquinones, anthanthrones, dianthraquinonyls, anthrapyrimidines, perylenes, perinones, quinacridones, thioindigo, dioxazines, isoindolinones, quinophthalones, azomethine azos, flavanthrones, diketopyrrolopyrroles, isoindolines, indanthrones, and carbon blacks. Further examples include carmine 6B, lake red C, permanent red 2B, disazo yellow, pyrazolone orange, carmine FB, chromophthalic yellow, chromophthalic red, phthalocyanine blue, phthalocyanine green, dioxazine violet, quinacridone magenta, quinacridone red, indanthrone blue, pyrimidine yellow, thioindigo bordeaux, thioindigo magenta, perylene red, perinone orange, isoindolinone yellow, aniline black, diketopyrrolopyrrole red, and daylight fluorescent pigments.
[0062] The hue of the organic pigment is preferably at least one selected from the group consisting of black pigments, indigo pigments, green pigments, red pigments, purple pigments, yellow pigments, orange pigments, and brown pigments, and more preferably at least one selected from the group consisting of black pigments, indigo pigments, red pigments, and yellow pigments.
[0063] Specific examples of organic pigments are shown by their Colour Index International (CI) numbers. Preferably, CI Pigment Red 57:1, CI Pigment Red 48:1, CI Pigment Red 48:2, CI Pigment Red 48:3, CI Pigment Red 146, CI Pigment Red 242, CI Pigment Yellow 83, CI Pigment Yellow 14, CI Pigment Orange 38, CI Pigment Orange 13, CI Pigment Yellow 180, CI Pigment Yellow 139, CI Pigment Red 185, CI Pigment Red 122, CI Pigment Red 178, CI Pigment Red 190, CI Pigment Red 200, CI Pigment Red 210, CI Pigment Red 222, CI Pigment Red 230, CI Pigment Red 242, CI Pigment Yellow 83, CI Pigment Yellow 14, CI Pigment Orange 38, CI Pigment Orange 13, CI Pigment Yellow 180, CI Pigment Yellow 139, CI Pigment Red 185, CI Pigment Red 122, CI Pigment Red 178 ... and C.I. Pigment Red 149, C.I. Pigment Red 144, C.I. Pigment Red 166, C.I. Pigment Violet 23, C.I. Pigment Violet 37, C.I. Pigment Blue 15, C.I. Pigment Blue 15:1, C.I. Pigment Blue 15:2, C.I. Pigment Blue 15:3, C.I. Pigment Blue 15:4, C.I. Pigment Blue 15:6, C.I. Pigment Green 7, C.I. Pigment Orange 34, C.I. Pigment Orange 64, and C.I. Pigment Black 7. It is preferable to use one or more of these.
[0064] Inorganic pigments Examples of inorganic pigments include titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, aluminum particles, mica, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, iron black, titanium oxide, and zinc oxide. Aluminum can be either leafing or non-leafing type, with the non-leafing type being preferred.
[0065] The inorganic pigment preferably contains titanium oxide. The titanium oxide may have a crystal structure of any of anatase type, rutile type, and brookite type, and two or more types may be used in combination. Among them, rutile type titanium oxide is preferably used because of its excellent pigment dispersibility. In addition, in order to improve printability in gravure printing, it is preferable that the titanium oxide is surface-treated, and in particular, that the titanium oxide is surface-treated with at least one metal selected from the group consisting of Si, Al, Zn, Zr and oxides thereof.
[0066] The titanium oxide preferably has an oil absorption of 14 to 35 ml / 100 g, more preferably 17 to 32 ml / 100 g, as measured in accordance with JIS K5101, and more preferably has an average particle size (median particle size) of 0.2 to 0.3 μm as measured by a transmission electron microscope.
[0067] 《Extender pigment》 As the extender pigment, silica, barium sulfate, kaolin, clay, calcium carbonate, magnesium carbonate, etc. are preferably used.
[0068] (binder resin) The binder resin is not particularly limited and can be appropriately selected from known resins used in printing inks. Examples of such binder resins include polylactic acid resins, urethane resins, cellulose-based resins, polyamide resins, vinyl chloride resins, vinyl chloride-vinyl acetate copolymer resins, vinyl chloride-acrylic copolymer resins, castor oil-based resins, rosin-based resins, vinyl acetate resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, urethane-acrylic resins, styrene resins, styrene-acrylic acid resins, styrene-allyl alcohol copolymer resins, styrene-maleic acid copolymer resins, maleic anhydride resins, maleic acid resins, rosin-modified maleic acid resins, cycloolefin resins, dammar resins, polyester resins, alkyd resins, terpene resins, phenol-modified terpene resins, ketone resins, cyclized rubbers, chlorinated rubbers, butyral, polyacetal resins, silicone resins, and modified resins thereof, and one type can be used alone or two or more types can be mixed together. The printed layer preferably contains a cellulose-based resin (B) as a binder resin.
[0069] (Cellulosic resin (B)) As the cellulose-based resin (B), a cellulose ester resin is suitable. The cellulose ester resin is a resin obtained by esterification of cellulose derived from non-edible plants such as wood fiber and cotton, and examples of the cellulose ester resin include cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, and nitrocellulose. As the cellulose ester resin, nitrocellulose is preferred from the viewpoint of heat resistance. For the cellulose-based resin (B) and suitable embodiments thereof, the description in the above section (Cellulose-based resin (A)) can be cited.
[0070] The content of the cellulose-based resin (B) in the resin contained in the printed layer is preferably 30 to 99 mass%, more preferably 50 to 99 mass%, and particularly preferably 80 to 99 mass%. When it is in the above range, the hardness and toughness of the printed layer can be compatible, and blocking resistance and heat resistance are improved.
[0071] (Resin (C)) The printing layer preferably further contains, as a binder resin, at least one resin (C) selected from the group consisting of polyamide resins, urethane resins, styrene-maleic acid copolymer resins, styrene-allyl alcohol copolymer resins, and acrylic resins. Among these, the resin (C) preferably contains at least one selected from the group consisting of polyamide resins, urethane resins, and styrene-maleic acid resins, and more preferably contains a urethane resin.
[0072] {Urethane resin} The urethane resin preferably has a weight average molecular weight of 10,000 to 100,000, more preferably 20,000 to 80,000. The glass transition temperature is preferably 0° C. or lower, more preferably −60 to 0° C., and even more preferably −40 to −5° C. When it is in the above range, the printed layer can have both toughness and flexibility, resulting in good heat resistance and adhesion between the printed layer and the substrate. In addition, the urethane resin preferably has an amine value and / or a hydroxyl value, and the amine value is preferably 10 mgKOH / g or less, more preferably 5 mgKOH / g or less, and particularly preferably 3 mgKOH / g or less, in consideration of the browning that occurs when mixed with the cellulose-based resin (B). The hydroxyl value is preferably 0.5 to 30 mgKOH / g, more preferably 1 to 20 mgKOH / g. When it is in the above range, it is possible to achieve both adhesion to the substrate and affinity for the alcohol solvent, and the adhesion between the printing layer and the substrate and the alcohol bleeding resistance are improved.
[0073] The amine value is the number of milligrams of potassium hydroxide equivalent to the amount of hydrochloric acid required to neutralize the amino groups contained in 1 g of resin. The method for measuring the amine value is as follows. [Method for measuring amine value] Weigh out 5 to 10 g of sample (S: solid mass of sample in g). Add 25 mL of toluene and 25 mL of n-butanol to the weighed sample and dissolve thoroughly. Add 30 mL of methanol and perform potentiometric titration with 0.1 mol / L hydrochloric acid aqueous solution (titer: f). The titration amount (A mL) can be used to calculate the amine value using the following formula (1).
[0074] (Formula 1) Amine value = (A x f x 0.1 x 56.108) / S [mgKOH / g]
[0075] The hydroxyl value is the amount of hydroxyl groups in 1 g of resin calculated by acetylating the hydroxyl groups in the resin with an excess of an acetylating reagent and back titrating the remaining acid with an alkali, converted into mg of potassium hydroxide, and is in accordance with JIS K0070.
[0076] The urethane resin preferably contains structural units derived from polyether polyol and / or polyester polyol, and the total content thereof is preferably 10 to 50 mass%, more preferably 10 to 60 mass%, and even more preferably 5 to 80 mass%, based on 100 mass% of the urethane resin solid content. When it is in the above range, the printed layer can have both toughness and flexibility, resulting in good heat resistance and adhesion between the printed layer and the substrate. The urethane resin is not limited, but examples thereof include urethane resins obtained by reacting a urethane prepolymer having an isocyanate group at its terminal, which is obtained by reacting a polyol with a polyisocyanate, with a polyamine as a chain extender.
[0077] As the polyol, for example, various known polyester polyols, polyether polyols, etc. can be used, and one or more of each of them may be used in combination. Examples of the polyester polyol include polyester polyols obtained by dehydration condensation or polymerization of saturated or unsaturated low-molecular-weight polyols and polycarboxylic acids or anhydrides thereof; and polyester polyols obtained by ring-opening polymerization of cyclic ester compounds, such as lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone). Examples of the saturated or unsaturated low molecular weight polyols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3 propanediol, 2-ethyl-2-butyl-1,3 propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, 3-methyl-1,5 pentanediol, hexanediol, octanediol, 1,4-butynediol, 1,4-butylenediol, diethylene glycol, triethylene glycol, dipropylene glycol, glycerin, trimethylolpropane, trimethylolethane, 1,2,6-hexanetriol, 1,2,4-butanetriol, sorbitol, and pentaerythritol. Examples of the polyvalent carboxylic acid include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, trimellitic acid, and pyromellitic acid. Polyether polyols include, for example, polymers or copolymers of methylene oxide, ethylene oxide, propylene oxide, and tetrahydrofuran. Both the polyester polyol and the polyether polyol preferably have a branched structure.
[0078] Examples of the polyisocyanate include various known aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, etc. that are generally used in the production of urethane resins. These may form trimers to form an isocyanurate ring structure. Examples of aromatic diisocyanates include 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, and tolylene diisocyanate. Examples of the aliphatic diisocyanate include butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate. Examples of alicyclic diisocyanates include cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate, norbornane diisocyanate, m-tetramethylxylylene diisocyanate, hydrogenated 4,4-diphenylmethane diisocyanate, and dimer diisocyanate in which the carboxyl group of a dimer acid is converted into an isocyanate group. Among them, at least one selected from the group consisting of tolylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, bis(isocyanatomethyl)cyclohexane, hexamethylene diisocyanate, and a trimer of hexamethylene diisocyanate is preferred. These polyisocyanates can be used alone or in combination of two or more.
[0079] Examples of polyamines as chain extenders include ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, and dicyclohexylmethane-4,4'-diamine. In addition, polyamines having a hydroxyl group in the molecule, such as 2-hydroxyethylethylenediamine, 2-hydroxyethylpropyldiamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, and di-2-hydroxypropylethylenediamine, may be used as polyamines. These chain extenders may be used alone or in combination of two or more, with isophoronediamine being particularly preferred.
[0080] <Polyamide resin> The polyamide resin is not particularly limited, but is preferably a thermoplastic polyamide that is soluble in an organic solvent, and a polycondensation product of a polybasic acid and a polyamine is preferably used. Among these, polyamide resins containing a reaction product of an acid component containing polymerized fatty acid and / or dimer acid with an aliphatic and / or aromatic polyamine are preferred, and those containing a portion of primary and secondary monoamines are more preferred. As for the polyamide resin and suitable embodiments thereof, the description in the above section (Polyamide resin) can be cited.
[0081] Styrene-maleic acid copolymer resin The styrene-maleic acid copolymer resin can be obtained, for example, by radical copolymerization of a styrene monomer and a maleic acid monomer. The solid content mass ratio of the styrene monomer to the maleic acid monomer is preferably styrene monomer:maleic acid monomer=1:9 to 6:4, and more preferably 2:8 to 5:5.
[0082] The styrene-maleic acid copolymer resin has an acid value of preferably 150 to 300 mgKOH / g, more preferably 215 to 270 mgKOH / g. When the acid value of the styrene-maleic acid copolymer is 150 mgKOH / g or more, the halftone dot reproducibility tends to improve, and when it is 300 mgKOH / g or less, the solubility in a solvent increases, and the storage stability of the printing ink is excellent. The acid value is the number of mg of potassium hydroxide required to neutralize the acidic groups contained in 1 g of the resin solid content, and is based on JIS K 0070.
[0083] The glass transition temperature of the styrene-maleic acid copolymer resin is preferably 60 to 125°C, more preferably 70 to 105°C. When the glass transition temperature of the styrene-maleic acid copolymer is 60°C or higher, the printed layer becomes strong, and the heat resistance tends to be improved. When the glass transition temperature is 125°C or lower, the solubility in a solvent increases, and the storage stability of the printing ink is excellent. The weight average molecular weight is preferably 6,000 to 16,000, more preferably 10,000 to 15,000. When within the above range, the printed layer can have both toughness and flexibility, and the heat resistance and the adhesion between the printed layer and the substrate are improved.
[0084] Commercially available styrene-maleic acid copolymer resins include, for example, the XIRAN series (manufactured by Kawahara Oil Chemical Co., Ltd.) and the Alastar series (manufactured by Arakawa Chemical Co., Ltd.).
[0085] Styrene-allyl alcohol copolymer resin The styrene-allyl alcohol copolymer resin can be obtained, for example, by radical copolymerization of a styrene monomer and an allyl alcohol monomer. The solid mass ratio of the styrene monomer to the allyl alcohol monomer is preferably styrene monomer / allyl alcohol monomer=1 / 9 to 6 / 4, more preferably 2 / 8 to 5 / 5.
[0086] The styrene-allyl alcohol copolymer resin has a hydroxyl value of preferably 150 to 300 mgKOH / g, more preferably 180 to 250 mgKOH / g. When the hydroxyl value of the styrene-allyl alcohol copolymer is 100 mgKOH / g or more, the halftone dot reproducibility tends to improve, and when it is 50 mgKOH / g or less, the solubility in a solvent increases, and the storage stability of the printing ink tends to be excellent.
[0087] The glass transition temperature of the styrene-allyl alcohol copolymer resin is preferably 40 to 100°C, more preferably 50 to 80°C. When the glass transition temperature of the styrene-allyl alcohol copolymer is 40°C or higher, the printed layer tends to be tough and the heat resistance and abrasion resistance tend to be improved. When the glass transition temperature is 100°C or lower, the solubility in a solvent tends to be high, and the storage stability of the printing ink tends to be excellent. The weight average molecular weight of the styrene-allyl alcohol copolymer is preferably 1,000 to 5,000, more preferably 2,000 to 4,000. When within the above range, the printed layer can be made both tough and flexible, and the heat resistance, abrasion resistance, and adhesion between the printed layer and the substrate are improved. The acid value is preferably 50 to 300 mgKOH / g, more preferably 100 to 200 mgKOH / g.
[0088] Commercially available styrene-allyl alcohol resins include, for example, the SAA series (manufactured by Iyondellbasell).
[0089] Acrylic resin The acrylic resin is obtained by polymerizing a monomer having an unsaturated double bond containing a (meth)acrylic monomer in a solvent using a polymerization initiator. The glass transition temperature of the acrylic resin is preferably 40 to 110°C, more preferably 60 to 90°C. When the glass transition temperature of the acrylic resin is 40°C or higher, the toughness of the printed layer tends to increase and the heat resistance improves. When the glass transition temperature is 110°C or lower, the solubility in the solvent tends to increase and the storage stability of the printing ink is excellent. Further, the weight average molecular weight of the acrylic resin is preferably 5,000 to 100,000, more preferably 8,000 to 40,000. In the above range, the printed layer can achieve both toughness and flexibility, and the heat resistance and the adhesion between the printed layer and the substrate are improved.
[0090] The glass transition temperatures of the acrylic resin and the vinyl chloride-vinyl acetate copolymer resin can be measured by the differential scanning calorimeter (DSC measuring device, "DSC-60A" manufactured by Shimadzu Corporation) described in the section of the above-mentioned (nitrocellulose resin (A)), but can be estimated by the following FOX equation. <FOX equation> 1 / Tg = W1 / Tg1 + W2 / Tg2 + … + Wi / Tgi + … + Wn / Tgn 〔In the above FOX equation, the glass transition temperature of the homopolymer of each monomer constituting the polymer composed of n kinds of monomers is Tgi (K), and the mass fraction of each monomer is Wi, and (W1 + W2 + … + Wi + … Wn = 1).〕
[0091] Examples of the monomer having an unsaturated double bond including the (meth)acrylic monomer include alkyl ester compounds of (meth)acrylic acid such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, decyl (meth)acrylate, and lauryl (meth)acrylate; (meth)acrylic acid amide derivatives containing at least one N-substituted methylol group such as N-methylol (meth)acrylamide; dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and dipropylaminoethyl (meth)acrylate. aminoalkyl esters of (meth)acrylic acid such as dimethylaminopropyl (meth)acrylate, diethylaminopropyl (meth)acrylate, and dipropylaminopropyl (meth)acrylate; mono- or diesters of (meth)acrylic acid of glycols such as diethylene glycol and dipropylene glycol; styrene derivatives such as styrene and α-methylstyrene; hydroxyalkyl ester compounds of (meth)acrylic acid such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 3-hydroxypropyl (meth)acrylate; and vinyl compounds having an acid group such as acrylic acid, methacrylic acid, maleic acid, and itaconic acid. In terms of adhesion to paper substrates and surface protective layers, and heat resistance, the acrylic resin preferably has a carboxyl group and / or a hydroxyl group, and when the acrylic resin has a hydroxyl group, it preferably contains a hydroxyalkyl ester compound of (meth)acrylic acid as a monomer constituting the acrylic resin.
[0092] Commercially available acrylic resins include, for example, the DIANAL series (manufactured by Mitsubishi Rayon Co., Ltd.) and the ACRYDIC series (manufactured by DIC Corporation).
[0093] The mass ratio of the cellulose-based resin (B) to the resin (C) in the printed layer is preferably 99:1 to 30:70, more preferably 99:1 to 50:50, and even more preferably 99:1 to 80:20. When it is within the above range, the printed layer can have both hardness and toughness, and has improved puncture resistance, blocking resistance, and heat resistance.
[0094] The content of the binder resin in the printed layer is preferably 20 to 80% by mass, more preferably 40 to 60% by mass, in the printed layer. When it is in this range, the printed layer can have both hardness and flexibility, and the puncture resistance, blocking resistance, and adhesion between the printed layer and the paper base material are improved.
[0095] (Organic solvent) The printing ink may contain an organic solvent. Examples of the organic solvent that can be used include non-aromatic organic solvents such as hydrocarbons such as methylcyclohexane and ethylcyclohexane; ketones such as acetone, methyl ethyl ketone (MEK), and methyl isobutyl ketone; esters such as ethyl acetate, n-propyl acetate, and butyl acetate; and alcohols such as methanol, ethanol, propanol, isopropanol (IPA), and butanol. The organic solvent may be appropriately selected in consideration of reducing the amount of solvent remaining in the film after printing, and one type may be used alone, or two or more types may be mixed and used. As for the organic solvent and suitable embodiments thereof, the description in the above section [Overcoat agent] (organic solvent) can be cited.
[0096] (Other ingredients) The printing ink and printed layer may further contain additives such as pigment dispersants, isocyanate-based curing agents, chelating crosslinking agents, hydrocarbon wax particles, matting agents, finely powdered silica such as gas-phase silica, wet-process silica, organically treated silica, and alumina-treated silica, polyethylene wax, fatty acid amide wax, defoamers, leveling agents, plasticizers, infrared absorbers, ultraviolet absorbers, and flame retardants, provided the effects of the present invention are not impaired.
[0097] Pigment dispersant As the pigment dispersant, anionic, nonionic, cationic, amphoteric, or other surfactants can be used.
[0098] Isocyanate-based hardener As the isocyanate-based curing agent, polyisocyanate and modified compounds thereof can be used. Specifically, biuret, isocyanurate, and adduct of polyisocyanate are preferable, and diisocyanate is preferable as the polyisocyanate, and aromatic diisocyanate such as tolylene diisocyanate, alicyclic diisocyanate such as 1,4-cyclohexane diisocyanate and isophorone diisocyanate, aliphatic diisocyanate such as hexamethylene diisocyanate, and aromatic aliphatic diisocyanate such as α,α,α',α'-tetramethylxylylene diisocyanate are preferably used. Commercially available isocyanate-based curing agents include, for example, 24A-100, 22A-75, TPA-100, TSA-100, TSS-100, TAE-100, TKA-100, P301-75E, E402-808, E405-70B, AE700-100, D101, D201, A201H (manufactured by Asahi Kasei Corporation), Mytec Y260A (manufactured by Mitsubishi Chemical Corporation), Coronate CORONATE HX, Coronate CORONATE HL, Coronate CORONATE L (manufactured by Nippon Polyurethane Co., Ltd.), and Desmodur N75MPA / X (manufactured by Bayer). Among these, isophorone diisocyanate and an adduct and / or an isocyanurate of isophorone diisocyanate are preferred.
[0099] Chelating crosslinking agent The printing ink and the printed layer preferably contain a chelating crosslinking agent. For the chelating crosslinking agent and suitable embodiments thereof, the description in the above [Overcoat agent] <<Chelating crosslinking agent>> section can be used. The content of the chelating crosslinking agent in the printing layer is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass. When the content is 0.1% by mass or more, the heat resistance, oil resistance, and PVC blocking resistance are improved, and when the content is 5.0% by mass or less, the storage stability of the printing ink is excellent. By using these chelating crosslinking agents, the effect of improving the adhesion to the surface-coated paper substrate is achieved.
[0100] <Hydrocarbon wax particles> The printing ink and the printed layer preferably contain hydrocarbon wax particles. By containing the hydrocarbon wax particles, the adhesion to the paper substrate and the abrasion resistance of the printed layer are improved. For the hydrocarbon wax particles and suitable embodiments thereof, the description in the above [Overcoat agent] section "Hydrocarbon wax particles" can be used. In the overcoat agent, the average particle size of the hydrocarbon wax particles is preferably 0.3 to 10 μm, more preferably 0.8 to 7 μm, and the content of the hydrocarbon wax particles in the surface protective layer is preferably 0.1 to 10 mass %, more preferably 0.5 to 7 mass %.
[0101] Plasticizers The printing ink and the printed layer preferably contain a plasticizer. With a small amount of plasticizer, the plasticizer has the role of promoting the volatility of the organic solvent, imparting flexibility to the printed layer, and enhancing adhesion to the paper substrate. The description of the above-mentioned [Overcoat agent] (plasticizer) can be used for the plasticizer and its suitable embodiment. The printing layer in the present invention preferably contains, as a plasticizer, at least one plasticizer selected from the group consisting of castor oil, glycol ether, aliphatic dibasic acid ester, and tributyl acetyl citrate, and castor oil is more preferred. The content of the plasticizer in the printed layer is preferably 0.1 to 15% by mass, more preferably 5 to 15% by mass, and even more preferably 11 to 15% by mass. When it is within the above range, the printed layer can have both hardness and toughness, and the blocking resistance and heat resistance are improved.
[0102] <Heat seal layer> The heat seal layer in the present invention is located on the paper substrate opposite to the surface having the printing layer. The heat seal layer contains at least one selected from the group consisting of ethylene-vinyl acetate copolymer resin, acrylic resin, and ethylene-based ionomer. The resin contained in the heat seal layer may contain urethane resin, polyethylene resin, polypropylene resin, etc., in addition to ethylene-vinyl acetate copolymer resin, acrylic resin, and ethylene-based ionomer. These may be used alone or in combination of two or more. Among the above, the heat seal layer is preferably an ethylene-vinyl acetate copolymer resin and / or an ethylene-based ionomer, and more preferably an ethylene-vinyl acetate copolymer resin.
[0103] <Ethylene-vinyl acetate copolymer resin> The ethylene-vinyl acetate copolymer resin is a copolymer made of ethylene and vinyl acetate. The vinyl acetate content in the ethylene-vinyl acetate copolymer resin is preferably 5 to 50 mass%, more preferably 10 to 40 mass%, and particularly preferably 20 to 30 mass%, based on 100 mass% of the ethylene-vinyl acetate copolymer resin. The minimum film-forming temperature of the ethylene-vinyl acetate copolymer resin is preferably 40 to 120°C, more preferably 60 to 100°C. When the vinyl acetate content and the minimum film-forming temperature are within the above ranges, the heat sealability is good. The glass transition temperature of the ethylene-vinyl acetate copolymer resin is preferably -60 to 20°C, more preferably -25 to 5°C.
[0104] Examples of the ethylene-vinyl acetate copolymer resin that can be used include Aquatex EC series manufactured by Japan Coating Resins Co., Ltd. and Sumikaflex S-201HQ, S-305, S-305HQ, S-400HQ, S-401HQ, S-408HQE, S-450HQ, S-455HQ, S-456HQ, S-460HQ, S-467HQ, S-470HQ, S-480HQ, S-510HQ, S-520HQ, S-752, and S-755 manufactured by Sumitomo Chemical Co., Ltd.
[0105] <Acrylic resin> The acrylic resin is a resin containing a structural unit derived from an acrylic monomer. The acrylic resin is preferably an ethylene acrylic resin, and further, the acrylic resin preferably has a carboxyl group or other acidic group. The acid value of the acrylic resin is preferably 20 to 120 mgKOH / g, more preferably 30 to 100 mgKOH / g, and particularly preferably 40 to 80 mgKOH / g. When the acid value of the acrylic resin is 20 mgKOH / g or more, the recyclability is good, and when it is 120 mgKOH / g or less, the blocking resistance is good. The glass transition temperature of the acrylic resin is preferably -40 to 90°C, more preferably -30 to 70°C, and particularly preferably -20 to 50°C. When the glass transition temperature of the acrylic resin is in the above range, the blocking resistance and heat sealability are good. In addition, the acrylic resin may preferably be a homopolymer of an acrylic monomer, a copolymer of an acrylic monomer and an acidic monomer, or a copolymer of ethylene and an acrylic monomer.
[0106] Examples of the monomer having an unsaturated double bond including the (meth)acrylic monomer include alkyl ester compounds of (meth)acrylic acid such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, decyl (meth)acrylate, and lauryl (meth)acrylate; (meth)acrylic acid amide derivatives containing at least one N-substituted methylol group, such as N-methylol (meth)acrylamide; Aminoalkyl esters of (meth)acrylic acid such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dipropylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminopropyl (meth)acrylate, and dipropylaminopropyl (meth)acrylate; Mono- or diesters of (meth)acrylic acid of glycols such as diethylene glycol and dipropylene glycol, Styrene, α-methylstyrene and other styrene derivatives, Hydroxyalkyl ester compounds of (meth)acrylic acid, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 3-hydroxypropyl (meth)acrylate; Acrylic acid, methacrylic acid, Examples of suitable vinyl compounds include those having an acid group such as maleic acid and itaconic acid. From the viewpoint of heat sealability, the acrylic resin preferably has a carboxyl group and / or a hydroxyl group, and when the acrylic resin has a hydroxyl group, it preferably contains a hydroxyalkyl ester compound of (meth)acrylic acid as a monomer constituting the acrylic resin.
[0107] The acrylic resin may be a commercially available product, for example, JONCRYL PDX7356, PDX-7326, PDX-7430 manufactured by BASF, PE-1126, JE-1113, KE1148 manufactured by Seiko PMC Corporation, etc.
[0108] <Ethylene-based ionomer> The ethylene-based ionomer refers to a copolymer of ethylene and (meth)acrylic acid, etc., which has an ionized structure. It is preferable that the resin form is intermolecularly bonded by metal ions. For example, metal salts of ethylene-methacrylic acid copolymers, metal salts of ethylene-acrylic copolymers, metal salts of ethylene-urethane copolymers, metal salts of ethylene-fluorine polymers, etc. are all called ethylene-based ionomers. Examples of metal ions that form salts include alkali metal ions and alkaline earth metal ions, specifically, sodium, potassium, calcium, magnesium, and zinc ions. The minimum film-forming temperature of the ethylene-based ionomer resin is preferably 20 to 100°C, more preferably 40 to 80°C. When the minimum film-forming temperature is within the above range, the heat sealability is good.
[0109] As the ethylene-based ionomer, for example, Chemipearl S100, S111, S120, S650, S200, S300, S420, and S500 manufactured by Mitsui Chemicals can be used.
[0110] <Paper base material> The paper substrate is not particularly limited, and any known paper substrate can be used. Examples of such paper substrates include medium-quality paper, fine paper, newsprint, Yupo paper, various coated papers, lining paper, impregnated paper, cardboard, art paper, cast paper, kraft paper, coated board, ivory paper, card paper, cup base paper, cast paper, light-shielding paper, and surface-treated paper substrates thereof. The paper substrate may be a vapor-deposited paper on which a metal oxide such as silica or alumina, or a metal such as aluminum (collectively referred to as an inorganic compound) is vapor-deposited. In order to form a vapor-deposited layer uniformly on the paper substrate, the vapor-deposited paper may have an anchor layer between the paper substrate and the vapor-deposited layer, and the vapor-deposited layer may be coated with polyvinyl alcohol or the like. The thickness of the paper base material is preferably 50 to 150 g / m 2 , more preferably 60 to 120 g / m 2 , more preferably 60 to 90 g / m 2 It is.
[0111] <Barrier layer> The packaging material of the present invention preferably further comprises a barrier layer. The barrier layer is preferably disposed between the paper base layer and the print layer, and preferably contains an inorganic compound such as aluminum, alumina, silica, etc. The purity of the inorganic compound is preferably 99% or more, more preferably 99.9% or more. The method for forming the barrier layer is not particularly limited, and an inorganic compound layer can be formed on the paper substrate by a known method such as a vacuum deposition method, a sputtering method, etc. In addition, a barrier layer can be provided on the paper substrate by using the above-mentioned vapor-deposited paper. The vacuum deposition method uses high-frequency induction heating, direct current heating, electron beam heating, etc., and is performed at 1200 to 1500 °C for 10 -1 ~10 -2The deposition is carried out under conditions of about Pa. Before vacuum deposition, the object to be deposited may be subjected to a treatment for improving adhesion, such as a corona discharge treatment, on the surface. From the viewpoints of barrier properties, light-shielding properties, and economical efficiency, the thickness of the inorganic compound film formed by vacuum deposition is preferably 10 to 300 nm. The sputtering method is -1 ~10 -2 The deposition is carried out by introducing an inert gas such as Ar and applying a voltage under conditions of about Pa. The thickness of the inorganic compound film formed is preferably 10 to 300 nm from the viewpoints of barrier properties, light-shielding properties, and economic efficiency.
[0112] <Manufacturing method of packaging materials> The packaging material of the present invention can be obtained by the steps of printing a printing ink on one side of a paper base material to form a printed layer, printing an overcoat agent containing a cellulose-based resin (A) and a plasticizer on the printed layer to form a surface protective layer, and coating the other side of the paper base material with a heat seal agent to form a heat seal layer. In the above steps, the timing of the step of forming the heat seal layer is not particularly limited, but it is preferable to form the printing layer, the surface protective layer, and the heat seal layer in this order.
[0113] The printing layer and the surface protective layer are preferably formed by gravure printing or flexographic printing, with gravure printing being preferred, as gravure printing enables high-speed printing and significantly improves productivity.
[0114] The packaging material of the present invention may have a heat seal layer, a paper base material, a printing layer, and a surface protection layer in this order, and may further have another layer such as the above-mentioned barrier layer depending on the required performance. The laminate structure of the packaging material can be preferably as follows. Heat seal layer / paper base material / printing layer / surface protection layer Heat seal layer / barrier layer / paper base material / printing layer / surface protection layer Heat seal layer / paper base material / barrier layer / printing layer / surface protection layer Heat seal layer / paper base material / printing layer / barrier layer / surface protection layer EXAMPLES
[0115] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, "parts" and "%" represent "parts by mass" and "% by mass" unless otherwise noted. In addition, "NV." represents the mass % of non-volatile content.
[0116] <Preparation of cellulose-based resin solution> (Preparation Example 1) Preparation of nitrocellulose resin solution NC1 72 parts of nitrocellulose nc1 (manufactured by NOBEL, product name NC DHX 5-10, NV.70% (solvent: isopropyl alcohol), weight average molecular weight: 10,000, viscosity at 25.0% solution concentration: 2 seconds) was mixed and dissolved in 33.6 parts of ethyl acetate and 33.6 parts of isopropyl alcohol to obtain a nitrocellulose resin solution (NC1) with a solid content of 30%.
[0117] (Preparation Examples 2 to 4) Preparation of nitrocellulose resin solutions NC2 to NC4 Nitrocellulose resin solutions NC2 to NC5 were obtained in the same manner as in Preparation Example 1, except that the raw materials described below were used. Note that nc4 does not satisfy any of the above-mentioned preferable viscosity ranges (1) to (3). (NC2) Nitrocellulose nc2 (NOBEL, product name NC DHX 4-6, NV.70% (solvent: isopropyl alcohol), viscosity at 25.0% solution concentration: 1.2 seconds) (NC3) Nitrocellulose nc3 (NOBEL, product name NC DHX 30-50, NV.70% (solvent: isopropyl alcohol), viscosity at 25.0% solution concentration: 10 seconds) (NC4) Nitrocellulose nc4 (NOBEL, product name NC DHL 120-170, NV.70% (solvent: isopropyl alcohol), viscosity at 12.2% solution concentration: 20 seconds,)
[0118] (Preparation Example 3) Preparation of Cellulose Acetate Butyrate Resin Solution CAB1 72 parts of cellulose acetate butyrate (manufactured by EASTMAN CHEMICAL, product name CAB553-0.4, NV.70% (solvent: isopropyl alcohol), glass transition temperature: 136°C, weight average molecular weight: 20,000) was mixed and dissolved in 33.6 parts of ethyl acetate and 33.6 parts of isopropyl alcohol to obtain a cellulose acetate butyrate resin solution (CAB1) with a solid content of 30%.
[0119] <Adjustment of resin solution> (Preparation Example 4) Preparation of polyamide resin solution PA1 30 parts of polyamide resin pa1 (manufactured by Tsuno Foods Co., Ltd., product name Vegichem Green 725, NV. 100%, softening point 116°C, weight average molecular weight 8,000) and 70 parts of isopropyl alcohol were charged and dissolved at 50°C for 2 hours under a nitrogen stream to obtain a polyamide resin solution (PA1) with a solid content of 30%.
[0120] (Preparation Example 5) Preparation of polyamide resin solutions PA2 and PA3 Polyamide resin solutions PA2 and PA3 having a solid content of 30% were obtained in the same manner as in Preparation Example 4, except that the raw materials described below were used. (PA2) Polyamide resin pa2 (Harima Chemicals, product name: Newmide 846, NV.100%, softening point 110℃) (PA3) Polyamide resin pa3 (Harima Chemicals, product name Newmide 872, NV.100%, softening point 112℃)
[0121] (Preparation Example 6) Preparation of styrene-maleic acid copolymer resin solution SMA1 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube was charged with 50 parts of styrene-maleic acid copolymer resin (manufactured by Kawahara Oil Chemical Co., Ltd., product name XIRAN2625P, NV. 100%, glass transition temperature 110°C, weight average molecular weight 9,000, acid value 270 mgKOH / g), 33.3 parts of ethyl acetate, and 33.3 parts of isopropyl alcohol, and dissolved at 50°C for 2 hours under a nitrogen stream, to obtain a styrene-maleic acid copolymer resin solution (SMA1) with a solid content of 30%.
[0122] (Preparation Example 7) Preparation of styrene-allyl alcohol resin solution SA1 30 parts of styrene-allyl alcohol resin (manufactured by Iyondellbasell, product name SAA-100, NV. 100%, hydroxyl value: 205 mg KOH / g, weight average molecular weight 3,100) and 70 parts of ethyl acetate were charged and dissolved at 50°C for 2 hours under a nitrogen stream to obtain a styrene-allyl alcohol copolymer resin solution (SA1) with a solid content of 30%.
[0123] (Preparation Example 8) Preparation of acrylic resin solution AC1 30 parts of acrylic resin (manufactured by Gifu Ceramics Co., Ltd., product name TSA-28, NV. 100%, weight average molecular weight 10,000, acid value 195 mgKOH / g) and 70 parts of ethyl acetate were charged and dissolved at 50°C for 2 hours under a nitrogen stream to obtain an acrylic resin solution (AC1) with a solid content of 30%.
[0124] (Preparation Example 9) Preparation of vinyl chloride-vinyl acetate copolymer resin solution PVC1 30 parts of vinyl chloride-vinyl acetate copolymer resin (manufactured by Nissin Chemical Industry Co., Ltd., product name Solvine TA5R, NV.100%, glass transition temperature 78°C, weight average molecular weight 61,000) and 70 parts of ethyl acetate were charged and dissolved at 50°C for 2 hours under a nitrogen stream to obtain a vinyl chloride-vinyl acetate copolymer resin solution (PVC1) with a solid content of 30%.
[0125] (Preparation Example 10) Preparation of urethane resin solution PU1 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube was charged with 257.86 parts of poly(1,2-propylene glycol) having a number average molecular weight of 2,000 (hydroxyl value: 56.1 mg KOH / g), 18.01 parts of isophorone diisocyanate, 20.27 parts of diphenylmethane diisocyanate, 0.03 parts of tin (II) 2-ethylhexanoate, and 200 parts of ethyl acetate, and the mixture was reacted at 90° C. for 3 hours under a nitrogen stream to obtain 496.14 parts of a solution of a terminal isocyanate prepolymer. Next, a mixture of 3.86 parts of isophorone diamine, 280 parts of isopropyl alcohol, and 220 parts of ethyl acetate was gradually added to the obtained solution of isocyanate-terminated prepolymer at room temperature, and then the mixture was reacted at 50°C for 1 hour to obtain a urethane resin solution (PU1) with a solid content of 30%, a weight average molecular weight of 78,000, and an amine value of undetectable (less than 0.1 mgKOH / g).
[0126] (Preparation Example 11) Preparation of chlorinated rubber resin solution CG1 30 parts of chlorinated rubber resin CG1 (manufactured by Sumika Bayer Urethane Co., Ltd., product name Pergod S20, NV. 100%) and 70 parts of ethyl acetate were charged and dissolved at 50°C for 2 hours under a nitrogen stream to obtain a chlorinated rubber resin solution (CG1) with a solid content of 30%.
[0127] <Printing ink manufacturing> (Production Example 1) Production of Printing Ink K1 86 parts of Lionol Yellow TT1405G (manufactured by Toyo Color Co., Ltd., NV 100%), 386 parts of nitrocellulose resin solution NC1, 57 parts of urethane resin solution PU1, 140 parts of N-propyl acetate, 40 parts of ethyl acetate, and 30 parts of isopropyl alcohol were stirred and mixed, and the pigment was dispersed using a bead mill (using zirconia beads), and then 193 parts of nitrocellulose resin solution NC1, 93 parts of N-propyl acetate, 18 parts of ethyl acetate, 35 parts of isopropyl alcohol, 40 parts of polyethylene wax (NV 15%, solvent: ethyl acetate), 20 parts of diethylene glycol monobutyl ether (NV 100%), 16 parts of castor oil plasticizer (NV 100%), and 40 parts of titanium chelate (NV 50%, solvent: ethyl acetate) were stirred and mixed to obtain printing ink K1.
[0128] (Production Examples 2 to 17) Production of Printing Inks K2 to 17 Printing inks K2 to K17 were obtained in the same manner as in Production Example 1, except that the raw materials and compounding ratios shown in Table 1 were used.
[0129] <Production of overcoat agent> (Production Example 18) Production of overcoat agent V1 Overcoat agent V1 was obtained by stirring and mixing 65.5 parts of nitrocellulose resin solution NC1, 5.5 parts of N-propyl acetate, 3 parts of ethyl acetate, 5.5 parts of isopropyl alcohol, 5.4 parts of methylcyclohexane, 0.9 parts of methylpropylene glycol, 0.9 parts of water, 1.85 parts of diethylene glycol monobutyl ether (NV 100%), 8.3 parts of polyethylene wax (NV 15%, solvent: ethyl acetate), and 3 parts of hexamethylene bisoleic acid amide (NV 100%).
[0130] (Production Examples 19 to 33, Comparative Production Examples 1 to 3) Production of Overcoat Agents V2 to 19 Overcoat agents V2 to 19 were obtained in the same manner as in Production Example 18, except that the raw materials and compounding ratios shown in Table 2 were used.
[0131] (Heat sealant H1~H5) H1: Heat sealant containing ethylene vinyl acetate copolymer resin (Japan Coating Resins, Aquatex MC3800, minimum film-forming temperature: 100°C, solid content 50% by mass) H2: A heat sealant containing acrylic resin (acid value 100 mgKOH / g, glass transition temperature 20°C, solid content 48% by mass) H3: Heat sealant containing ethylene acrylic copolymer resin (Japan Coating Resins, Aquatex AC3100, minimum film-forming temperature: 100°C, solid content 44.5% by mass) H4: Heat sealant containing ethylene ionomer (Mitsui Chemicals, Chemipearl S100, minimum film-forming temperature: 65°C, solid content 27% by mass) H5: Heat sealant containing urethane resin (solid content 30%, hydroxyl value 3.8 mgKOH / g, amine value 8.5 mgKOH / g, weight average molecular weight 48,000)
[0132] <Manufacturing of packaging materials> (Example 1) Production of packaging material P1 Printing ink K1 and overcoat agent V4 were diluted with a mixed solvent of ethyl acetate:isopropyl alcohol = 7:3 (mass ratio) and their viscosities were adjusted to 15 seconds at 25°C using a Zahn cup #3 (manufactured by Rigo Co., Ltd.). Next, Ryuo Coat Paper (manufactured by Daio Paper Co., Ltd., base material width 125 mm, basis weight 65 g / m 2 ) coated surface, vacuum level 8 x 10 -1 A barrier layer was formed by vacuum deposition of aluminum (purity 99.9% or more) under the condition of a coating thickness of 20 μm. A printed layer was formed by printing diluted printing ink K1 on the barrier layer using a gravure printing machine equipped with a gravure plate having a plate depth of 30 μm under the conditions of a printing speed of 50 m / min and an in-line oven temperature of 60° C., and then an overcoat agent V4 was printed on the printed layer using a gravure printing machine equipped with a gravure plate having a plate depth of 30 μm under the conditions of a printing speed of 50 m / min and an in-line oven temperature of 60° C., to obtain an intermediate laminate p1 having a configuration of paper substrate / barrier layer / printed layer / surface protective layer. A heat seal agent H1 was printed on the side of the substrate opposite the printing layer in the intermediate laminate p1 using a gravure printing machine equipped with a gravure plate with a plate depth of 50 μm at a printing speed of 50 m / min and an in-line oven temperature of 70°C to obtain a packaging material P1 having a configuration of heat seal layer / paper substrate / barrier layer / printed layer / surface protection layer.
[0133] (Examples 2 to 40, Comparative Examples 1 to 6) Production of packaging materials P2 to P46 Packaging materials P2 to P46 having the configurations shown in Table 3 were produced in the same manner as in the production of packaging material P1, except that the printing ink, overcoat agent, and heat seal agent shown in Table 3 were used. The properties of the raw materials used are as follows. Kraft paper (Nippon Paper Industries, double glazed Kraft K, basis weight 100g / m 2 )
[0134] <Evaluation of packaging materials> The resulting packaging material was evaluated as described below, and the results are shown in Table 3.
[0135] (Puncture resistance) The obtained packaging material was cut into 70 mm squares and tested under the following conditions using a method based on JIS1707, and evaluated according to the following criteria, where A, B, and C are ranges that are acceptable for practical use. <Penetration test conditions> Piercing speed: 50mm / min, needle diameter: 1mm, Needle piercing surface: overcoat surface of second laminate Evaluation Criteria A. The puncture strength is 12N or more. B. The puncture strength is greater than or equal to 10N and less than 12N. C. The puncture strength is 5N or more and less than 10N. D. The puncture strength is less than 5N.
[0136] (Blocking resistance) The obtained packaging material was cut into two pieces of 40 mm square, and the heat seal layer surface of one packaging material piece was completely overlapped with the surface protection layer surface of the other packaging material piece, and the temperature was 40°C, humidity was 80% RH, and a load of 100 N / cm was applied. 2 After leaving it for 24 hours, the two overlapping packaging materials were peeled off, and the peeling state of the printed layer was visually observed and evaluated according to the following criteria. A, B, and C are ranges that are acceptable for practical use. Evaluation Criteria A. No transfer of the printing layer to the heat seal layer surface is observed. B. The amount of the printed layer transferred to the heat seal layer surface is more than 0 area % and less than 10 area %. C. The amount of the printed layer transferred to the heat seal layer surface is 10% by area or more and less than 30% by area. D. The amount of the printed layer transferred to the heat seal layer surface is 30% or more by area.
[0137] (Water friction resistance) The obtained packaging material was cut into a size of 25 mm x 150 mm, and the water friction resistance was evaluated according to the following criteria using a Gakushin-type friction fastness tester manufactured by Tester Sangyo Co., Ltd. Note that A, B, and C are ranges that are acceptable for practical use. Test conditions: Load: 200g, number of reciprocations: 2, paper: 5 drops of water on Kanakin cloth Evaluation Criteria A. The printed layer is not removed and the exposed area of the base paper is less than 1%. B. The paper has a small amount of ink on it. A small amount of the printing layer has been removed, and the exposed area of the base paper is between 1% and 10%. C. The paper has a thin layer of ink on the entire surface. The printed layer has been removed slightly, and the exposed area of the base paper is between 10% and 20%. D. The ink is thickly adhered to the entire surface of the paper. Most of the printing layer has been removed, and the exposed area of the base paper is 20% or more.
[0138] (Heat resistance) The obtained packaging material was cut into a size of 15 mm x 100 mm, and a glossy aluminum foil (thickness: 15 microns) of 15 mm x 100 mm was placed on the surface protective layer, and heat-sealed using the following equipment and conditions. The aluminum foil was then peeled off, and the heat resistance was evaluated based on the peeling state of the printed layer according to the following criteria. A, B, and C are ranges that are acceptable for practical use. <Heat sealing conditions> Equipment: Thermal gradient heat sealer [Toyo Seiki Co., Ltd.; TYPE, HG-100], Seal width: 10mm from the bent part, heater temperature: 240℃, Sealing pressure: 2kg / cm 2 , Sealing time: 1sec Evaluation Criteria A. No peeling of the printed layer was observed. B. Less than 20% by area of the printed layer peeled off. C. More than 20% but less than 50% by area of the printed layer peeled off. D. More than 50% of the printed layer has peeled off.
[0139] (Heat sealability) The obtained packaging material was cut into a size of 15 mm x 100 mm, folded so that the heat-sealed layers overlapped each other, and heat-sealed using the following equipment and conditions. Both unsealed ends were fixed to a small tensile tester to evaluate the heat-seal strength. A, B, and C are ranges that are acceptable for practical use. <Heat sealing conditions> Equipment: Heat seal tester manufactured by Tester Sangyo Co., Ltd. Seal width: 10mm from the bent part, Heater temperature: 160℃, sealing pressure: 2kg / cm 2 , Sealing time: 1sec <Heat seal strength measurement> Equipment: Intesco small tensile testing machine (model: IM-20), test piece width: 15 mm, Peeling mode: 90° peeling, tensile speed: 300mm / min Evaluation Criteria A. The heat seal strength is 3.5N or more. B. The heat seal strength is greater than 2.5N and less than 3.5N. C. The heat seal strength is 1.0N or more and less than 2.5N. D. The heat seal strength is less than 1.0 N.
[0140] (Water vapor barrier properties) The resulting packaging material was measured for moisture permeability according to JIS Z0208 and evaluated according to the following criteria, where A, B, and C are ranges that are acceptable for practical use. Evaluation Criteria A. Moisture permeability is 5g / m 2 Less than 15 hours. B. Moisture permeability is 5g / m 2 ·15h or more, 1000g / m 2 Less than 15 hours. C. Moisture permeability is 1000g / m 2 ·15h or more, 3000g / m 2 Less than 15 hours. D. Moisture permeability is 3000g / m 2 -15 hours or more.
[0141] [Table 1]
[0142] [Table 2]
[0143] [Table 3]
[0144] [Table 3]
[0145] The present invention makes it possible to provide a packaging material and a packaging bag that are excellent in puncture resistance, blocking resistance, heat resistance, and water-friction resistance while maintaining heat sealability and water vapor barrier properties. In particular, Example 1, in which the surface protection layer contained nitrocellulose resin and polyamide resin in a mass ratio of 20.6:79.4, the printing layer contained nitrocellulose resin and urethane resin in a mass ratio of 87.1:12.9, and the heat seal layer contained ethylene-vinyl acetate copolymer resin, was excellent in puncture resistance, blocking resistance, water friction resistance, heat resistance, heat sealability, and water vapor barrier properties. On the other hand, Comparative Example 3, which did not contain a plasticizer in the surface protective layer, and Comparative Examples 4 and 5, which contained a urethane resin or a chlorinated rubber resin in the surface protective layer, did not meet the standards in terms of blocking resistance and heat resistance, and Comparative Example 6, which contained a urethane resin in the heat seal layer, did not meet the standards in terms of blocking resistance and heat resistance.
Claims
1. A packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, the heat seal layer comprises at least one selected from the group consisting of ethylene-vinyl acetate copolymer resins, acrylic resins, and ethylene-based ionomers; The packaging material, wherein the surface protective layer comprises a cellulose-based resin (A) and a plasticizer.
2. 2. The packaging material according to claim 1, wherein the surface protective layer has a gloss value of 15 or more as measured in accordance with JIS Z 8741.
3. 3. The packaging material according to claim 1, wherein the surface protective layer has a plasticizer content of 0.1 to 20% by mass.
4. 3. The packaging material according to claim 1, wherein the plasticizer comprises at least one plasticizer selected from the group consisting of citric acid esters, phthalic acid esters, phosphate esters, trimellitic acid esters, aliphatic dibasic acid esters, glycol ethers, sulfonic acid amides, and castor oil.
5. The packaging material according to claim 1 or 2, wherein the heat seal layer comprises an ethylene-vinyl acetate copolymer resin and / or an ethylene-based ionomer.
6. The packaging material according to claim 1 or 2, wherein the viscosity of the cellulose-based resin (A) measured in accordance with JIS K 6703 satisfies any one of the following (1) to (3). (1) The viscosity at a solution concentration of 12.2% by mass is 1.5 to 16 seconds. (2) The viscosity at a solution concentration of 20.0% by mass is 3.0 to 40 seconds. (3) The viscosity at a solution concentration of 25.0% by mass is 0.1 to 22 seconds.
7. The packaging material of claim 1 or 2, further comprising a barrier layer.
8. The packaging material according to claim 1 or 2, wherein the cellulose-based resin (A) comprises a nitrocellulose resin.
9. The packaging material according to claim 1 or 2, wherein the printed layer comprises a cellulose-based resin (B).
10. The packaging material according to claim 9, wherein the printed layer further contains at least one resin (C) selected from the group consisting of polyamide resins, urethane resins, styrene-maleic acid copolymer resins, styrene-allyl alcohol copolymer resins, and acrylic resins.
11. The packaging material according to claim 10, wherein the mass ratio of the cellulose-based resin (B) to the resin (C) is 99:1 to 30:
70.
12. The packaging material according to claim 1 or 2, wherein the surface protective layer further comprises a polyamide resin.
13. The packaging material according to claim 12, wherein the mass ratio of the cellulose-based resin (A) to the polyamide resin is 99:1 to 15:
85.
14. The packaging material according to claim 1 or 2, wherein the surface protective layer further comprises an amide wax.
15. A packaging bag formed from the packaging material according to claim 1 or 2.
16. A method for producing a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, comprising: A step of gravure printing a printing ink onto one side of a paper substrate to form a printing layer; A step of forming a surface protective layer by gravure printing an overcoat agent containing a cellulose-based resin (A) and a plasticizer on the printing layer; and A method for producing a packaging material, comprising a step of coating the other side of a paper substrate with a heat-sealing agent containing at least one selected from the group consisting of ethylene-vinyl acetate copolymer resin, acrylic resin, and ethylene-based ionomer to form a heat-sealing layer.
Citation Information
Patent Citations
Paper-made laminate and paper-made container
JP2006256198A
Laminate and packaging product containing the same
JP2018051796A
Packaging material and packaging product
JP2020055171A